Florecitas en su jardin - Grundemann, Sabine (Mexico : Grundemann, Sabine, 2009)
Margarita lives in a typical Mexican family where the role and position of women is set by rather traditional patriarchal rules. Margarita, a rebel herself, questions these values and points out the flaws of a society that opresses women, setting a negative example to boys and young men of future generations as well.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films